Large Reductions in Match Play Physical Performance Variables Across a Professional Football Season With Control for Situational and Contextual Variables - Springham, Matthew; Williams, Sean; Waldron, Mark; Burgess, Darren; Newton, Robert Usher (Frontiers in Sports and Active Living, 2020)
This investigation examined match play physical performance across a professional football season using a multicamera computerized tracking system. A linear mixed-effects model, controlling for situational and contextual variables, identified decreases in team average total distance (TD): season quarter 1 (Q1) (11,047 m) > season quarter 2 (Q2) (10,473 m) (P = 0.002; ES = Small), season quarter 3 (Q3) (10,449 m) (P < 0.001; ES = Moderate), and season quarter 4 (Q4) (10,385 m) (P < 0.001; ES = Moderate); work rate (WR): Q1 (115 m/min) > Q3 (108 m/min) (P < 0.001; ES = Moderate), Q4 (107 m/min) (P < 0.001; ES = Moderate); Q2 (109 m/min) > Q4 (107 m/min) (P = 0.003; ES = Small); high-speed running distance (HSR): Q1 (1,051 m) > Q2 (813 m) (P = 0.006; ES = Small); number of high-speed runs (NHSR): Q1 (87) > Q2 (65) (P < 0.001; ES = Small), Q3 (64) (P = 0.002; ES = Small); sprint distance (SD): Q1 (202 m) > Q4 (130 m) (P < 0.001; ES = Moderate), Q2 (179 m) > Q3 (165 m) (P = 0.035; ES = Small), Q4 (130 m) (P < 0.001; ES = Moderate) and number of sprints (NS): Q1 (20.4) > Q3 (10.2) (P < 0.001; ES = Moderate), Q4 (8.3) (P < 0.001; ES = Large); Q2 (14.9) > Q3 (10.2) (P < 0.001; ES = Moderate), Q4 (8.3) (P < 0.001; ES = Large). Within-position changes were observed for WR: Q1 (122 m/min) > Q4 (113 m/min) (P = 0.002; ES = Large) in central midfielders and for NS: Q1 > Q3 in wide defenders (21.7 vs. 10.8) (P = 0.044; ES = Large) and central midfielders (18.1 vs. 8.3) (P = 0.002; ES = Large); Q1 > Q4 in central defenders (13.1 vs. 5.3) (P = 0.014; ES = Large), wide defenders (21.6 vs. 7.1) (P < 0.001; ES = Very Large), central midfielders (18.1 vs. 8.5) (P = 0.005; ES = Large), and wide midfielders (20.8 vs. 12.2) (P = 0.012; ES = Large); Q2 > Q3 in central midfielders (16.9 vs. 8.3) (P = 0.002; ES = Large) and Q2 > Q4 in wide defenders (16.3 vs. 7.1) (P = 0.005; ES = Very Large), central midfielders (16.9 vs. 8.5) (P = 0.004; ES = Large), and wide midfielders (20.8 vs. 12.2) (P = 0.007; ES = Large). The match-play physical performance was reduced across the competitive season. The most notable reductions were observed in wide defenders, central midfielders, and wide midfielders in sprint performance indices.